2010
DOI: 10.1021/ja106679z
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Dependent Catalytic Properties of Pt Nanoparticles

Abstract: Tailoring the chemical reactivity of nanomaterials at the atomic level is one of the most important challenges in catalysis research. In order to achieve this elusive goal, fundamental understanding of the geometric and electronic structure of these complex systems at the atomic level must be obtained. This article reports the influence of the nanoparticle shape on the reactivity of Pt nanocatalysts supported on γ-Al(2)O(3). Nanoparticles with analogous average size distributions (∼0.8-1 nm), but with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
349
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(360 citation statements)
references
References 47 publications
8
349
2
1
Order By: Relevance
“…Further details on the sample preparation method and synthesis parameters can be found in Refs. 28,38,[41][42][43][44] and Table I. Table I.…”
Section: Experimental and Theoretical Methods A) Sample Preparation Amentioning
confidence: 99%
See 2 more Smart Citations
“…Further details on the sample preparation method and synthesis parameters can be found in Refs. 28,38,[41][42][43][44] and Table I. Table I.…”
Section: Experimental and Theoretical Methods A) Sample Preparation Amentioning
confidence: 99%
“…50 Quantitative determination of the NP shape was carried out by analyzing low temperature EXAFS data up to the 4 th nearest neighbor contribution, including multiple scattering (MS), as described in Refs. 38,43 and references therein. The data were acquired in H 2 after NP reduction.…”
Section: B) Structural and Vibrational Characterization (Exafs) And Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements can be made to catalysts by forming non-equilibrium morphologies. 14,38,[49][50][51][52][53] Very recent results by Chen et al 13 have shown unprecedented capabilities of Pt x Ni ''nanoframes'' to catalyze oxygen reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal expansion behavior manifests different local structure in bismuth nanoparticles than that in bulk ones. In order to reveal the origin of this kind of unusual thermal expansion behaviors in nanosized bismuth, local structural information was extracted from EXAFS for its atomic selectivity and high sensitivity to the short‐range structure 31, 32, 33…”
mentioning
confidence: 99%